2010
DOI: 10.1097/ccm.0b013e3181c02ca1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impedance cardiogram recorded by an automated external defibrillator during clinical cardiac arrest*

Abstract: The impedance cardiogram algorithm is a significant marker of circulatory collapse. Automated defibrillators with an integrated impedance cardiogram could improve emergency care by lay persons, enabling rapid and appropriate initiation of external cardiac massage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…18,19,21 Combining ECG and ICC features improved the accuracy of the RLS based detector by over 7 points (see supplementary materials). The RLS filter we propose is a more efficient estimator of the ICC component than our previous LMS method, 22 and permits a reliable PEA/PR discrimination using shorter ECG/TI segments of duration below 5 s with minimal computational burden, around 50ms (see supplementary materials).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19,21 Combining ECG and ICC features improved the accuracy of the RLS based detector by over 7 points (see supplementary materials). The RLS filter we propose is a more efficient estimator of the ICC component than our previous LMS method, 22 and permits a reliable PEA/PR discrimination using shorter ECG/TI segments of duration below 5 s with minimal computational burden, around 50ms (see supplementary materials).…”
Section: Discussionmentioning
confidence: 99%
“…Cromie et al used a single feature computed from the spectrum of the processed TI as a clinical marker of circulatory collapse in animals 20 and humans. 21 In our previous work, we presented a reliable method to extract the impedance circulation component (ICC) using an adaptive processing scheme, and concluded that morphological features extracted from ICC showed great potential for PEA/PR discrimination. 22 …”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the features can be found in [7], [13], [14] and [15]. • TI features (30 from the TI and its $ − % coefficients and its combination with the ECG): the mean power of the TI and the mean cross-power between ECG and TI [16], the first-order derivative of the TI and the peak amplitude of the Fast Fourier Transform (FFT) of the first-order derivative of the TI [17], and the magnitudesquared coherence and the cross power spectral density of ECG and TI.…”
Section: Feature Extractionmentioning
confidence: 99%
“…That same year, Cromie et al showed in an animal model that the Fast Fourier Transform (FFT) of the impedance cardiogram recorded through defibrillation pads was a potential clinical marker of cardiac arrest [14]. In a subsequent clinical study, they refined the method and evaluated its performance with in-hospital cardiac arrest and nonarrest patients [15]. They concluded that selective filtering of the impedance cardiogram was a powerful hemodynamic sensor of cardiac arrest, with a sensitivity (specificity) of 81% (97%) in the validation set.…”
Section: State Of the Artmentioning
confidence: 99%